Diet quality and diet patterns in relation to circulating cardiometabolic biomarkers. Issue 2 (April 2016) - Ko, Byung-Joon; Park, Kyung Hee; Shin, Sangah; Zaichenko, Lesya; Davis, Cynthia R.; Crowell, Judith A.; Joung, Hyojee; Mantzoros, Christos S.
Summary: Background & aims: We examined the effects of diet quality and dietary patterns in relation to biomarkers of risk including leptin, soluble intracellular adhesion molecule 1 (sICAM-1), C-reactive protein (CRP), and irisin. Methods: We analyzed data from 196 adults cross-sectionally. Dietary patterns were identified by factor analysis and diet quality scores were generated using a validated food-frequency questionnaire. Results: Both the alternate healthy eating index-2010 (AHEI-2010) and the Dietary Approaches to Stop Hypertension (DASH) scores were negatively related to CRP, even after controlling for body mass index and total energy intake. Similarly, the prudent diet pattern was negatively related to leptin, sICAM-1, and CRP, whereas the Western diet pattern showed positive associations with these markers; however, after adjusting for all confounders, the associations only remained significant for leptin and sICAM-1. Irisin was positively associated with DASH and the prudent diet after controlling for all confounders (standardized β  = 0.23, P  = 0.030; standardized β  = 0.25, P  = 0.021, respectively). Irisin showed positive associations with increasing fruit consumption, whereas the levels of irisin decreased as meat consumption increased. Conclusions: Irisin was directly associated with healthy diet types and patterns. Further studies regarding these mechanisms are warranted. This trial is registered athttp://www.clinicaltrials.gov .Identifier :NCT01853332 .